Trends and Strategies of M-Commerce Implementation - Natalia SAVINA; Andrey KALCHUK (Communications of International Proceedings, 2021)
This article presents a comprehensive study of the global mobile commerce market and related trends. The aim is to determine the impact of the digital transformation of society and the economy, as well as the expansion of budget smartphones on the development of mobile commerce and to identify its main trends.The authors use reports and studies of companies devoted to the study of the current state of e-commerce and mobile commerce to analyze the dynamics of related indicators. The usage structure of e-commerce by device is compared, taking into account the age and regional criteria. As an empirical research, correlation analysis is used to assess the dependence of the dynamics of mobile commerce sales on a number of factors.The presented statistics illustrate the trends of mobile commerce: the growth of its share in e-commerce, the direct impact of the age of customers and the country of residence on the choice of device for online purchases. The authors point toincreasing the benefits for sellers from using of mobile applications, voice communication, social commerce andan augmented reality shopping.The paper concludes that the Chinese smartphone manufacturers are becoming the engine of mobile commerce. It is noted that it is important for entrepreneurs to use the main trends of mobile commerce using an omnical approach and taking into account the size of the company.
Keywords: Mobile Commerce; E-Commerce; Digital Economy; Entrepreneurship; World Economy Trends; Omnichannel.